2020
DOI: 10.2147/dddt.s227477
|View full text |Cite
|
Sign up to set email alerts
|

<p>Apatinib in Patients with Relapsed or Refractory Diffuse Large B Cell Lymphoma: A Phase II, Open-Label, Single-Arm, Prospective Study</p>

Abstract: These authors contributed equally to this work Purpose: Treatment options for relapsed or refractory diffuse large B-cell lymphoma (RR DLBCL) represent an unmet medical need. Apatinib is a new oral tyrosine kinase inhibitor mainly targeting vascular endothelial growth factor receptor-2 (VEGFR-2) to inhibit tumour angiogenesis. In the present study, we evaluated the efficacy and safety of apatinib for patients with RR DLBCL. Patients and Methods: In this phase II, open-label, single-arm, prospective study, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In addition, several recent phase II clinical trials have confirmed that apatinib monotherapy has certain efficacy and good safety in the treatment of advanced cholangiocarcinoma (ORR, 11.5%) (65), relapsed or refractory diffuse large B-cell lymphoma (ORR, 43.8%) (66), metastatic or locoregionally recurrent nasopharyngeal carcinoma (ORR, 36.4%) (67), and radioiodine-refractory differentiated thyroid cancer (ORR, 80%) (68). These clinical trials have only initially shown the efficacy and safety of apatinib in these malignancies (Table 6).…”
Section: Other Cancersmentioning
confidence: 99%
“…In addition, several recent phase II clinical trials have confirmed that apatinib monotherapy has certain efficacy and good safety in the treatment of advanced cholangiocarcinoma (ORR, 11.5%) (65), relapsed or refractory diffuse large B-cell lymphoma (ORR, 43.8%) (66), metastatic or locoregionally recurrent nasopharyngeal carcinoma (ORR, 36.4%) (67), and radioiodine-refractory differentiated thyroid cancer (ORR, 80%) (68). These clinical trials have only initially shown the efficacy and safety of apatinib in these malignancies (Table 6).…”
Section: Other Cancersmentioning
confidence: 99%
“…Apatinib is an orally administered novel tyrosine kinase inhibitor targeting vascular endothelial growth factor receptor-2 (VEGFR-2), which involves in lymphomagenesis. Home administration of apatinib with regular outpatient follow-up produced encouraging antitumor effects in r/r DLBCL in an open-label, single-arm, prospective study [ 106 ]. ORR of 43.8% and a disease control rate of 71.9% were reported, with a median DoR of 5.0 (95% CI 3.5–6.5) months ( n = 32).…”
Section: Molecular Pathway Inhibitorsmentioning
confidence: 99%
“…ORR of 43.8% and a disease control rate of 71.9% were reported, with a median DoR of 5.0 (95% CI 3.5–6.5) months ( n = 32). The most common toxicities of any grade were hypertension (62.5%), leukopenia (40.6%), and hand-foot syndrome (40.6%) [ 106 ]. The relatively high response rate attained by apatinib deserves future investigation of drug combination strategies.…”
Section: Molecular Pathway Inhibitorsmentioning
confidence: 99%
“…Apatinib is a novel, small molecule anti-angiogenesis agent that inhibits VEGFR-2, c-kit, Src, and Ret. Phase II clinical trials have shown that Apatinib has manageable side effects and promising efficacy against various solid tumors ( 21 – 23 ). Two case studies suggested that Apatinib could benefit patients with liposarcoma ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%